2008
DOI: 10.1097/med.0b013e3282f76728
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil in the treatment of dyslipidemia

Abstract: Omega-3 fatty acid treatment should be considered in patients with severe hypertriglyceridemia as well as in high-risk patients with an atherogenic lipoprotein phenotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Other studies using this mouse model also found that the plasma cholesterol levels depends on the lipid composition in the diet [11], [25]. The molecular mechanisms for LC n-3 PUFAs effects on lipid homeostasis and atherosclerosis in these mice have been suggested to involve reduced vascular inflammatory response [25] or an impaired clearance of circulating lipoproteins [26]. Decreased plasma VLDL levels was associated with reduced atherosclerosis in the Ldlr −/− mouse [27], which would support the latter hypothesis.…”
Section: Discussionsupporting
confidence: 58%
“…Other studies using this mouse model also found that the plasma cholesterol levels depends on the lipid composition in the diet [11], [25]. The molecular mechanisms for LC n-3 PUFAs effects on lipid homeostasis and atherosclerosis in these mice have been suggested to involve reduced vascular inflammatory response [25] or an impaired clearance of circulating lipoproteins [26]. Decreased plasma VLDL levels was associated with reduced atherosclerosis in the Ldlr −/− mouse [27], which would support the latter hypothesis.…”
Section: Discussionsupporting
confidence: 58%
“…171 There are as yet no published studies examining statin effects on vascular health (PWV or cIMT) in children or adolescents with CDO. Omega-3 fish oil therapy has been shown to be safe in adults, with some trials reporting that TG levels decreased by as much as 30% to 45%, with significant associated increases in HDL-C. 172 However, more recent reports have not shown a conclusive benefit of fish oil treatment. [173][174][175] Two recently published randomized controlled trials of omega-3 fish oil in adolescents showed a minimal decrease in TG levels but no change in LDL particle number or size, suggesting no significant benefit of fish oil treatment in children with CDO.…”
Section: Medication Therapy For Cdomentioning
confidence: 98%
“…Administration of fish oils rich in PUFAs either alone or as an adjunct therapy with statin administration is an effective therapy for dyslipidemia associated with type 2 diabetes [21, 42]. EPA and DHA are the major PUFAs contained in fish oils.…”
Section: Disscussionmentioning
confidence: 99%
“…N-3 PUFA have been shown to reduce lipogenic enzyme expression via down-regulation of SREBP-1c in rodent hyperinsulinemic models [1719]. These data form the basis for use of n-3 PUFA supplements in treating hypertriglyceridemia associated with human states of hyperinsulinemia, such as type 2 diabetes mellitus [20, 21]. …”
Section: Introductionmentioning
confidence: 99%